Improvement of pregnancy ratios in the mating of bitches carried out with the aid of rapid progesterone assay - Aytekin Günay; Ülgen Günay (Eurasian Journal of Veterinary Sciences)
This study was carried out whh th© aim ol improving the pregnancy ratio through determining the mating lime wilh the aid of mpid progesterone assay. Twenty-four healihy bitches from different breeds were used as material, The bitches were separated into two equal groups. Twelve bitches in the first group were mated between days 12-14 after prooestrus bleeding and their pregnancy ratios were evaluated. Twelve bitches in the second group were subjected to progesterone analyses via rapid progesterone assay alter the ratio ol superficial cells exceeded 80 % in the vaginal cytology applied following the onset of prooestrus. Five of the bilches with progesterone values between 2.5-8 ng/ml were mated once, and 7 of them were mated twice with 12-24 h intervals. Birth ratios of 0/12 and 10/12 were obtained in the firsl and second groups, respectively. Ratio of superficial cells was determined as 83.75+1.08 % in the period during which ooslrus started and the progesterone value was determined at C2 level; and as 90.08±1.01 % at C3 level during which the mating was realised (P<0.001). The density of superficial cells reached 80 % level 9.83+0.29 days after ihe onset of prooestrus Weeding. However, the progesterone level reached C3 level after 11.83+0.53 days, which is the suitable period for mating. The difference between these two values was found statistically significant (P<0.01). As a result, it was concluded that it could be possible to Improve the pregnancy ratio through determining the suitable day tor mating via rapid progesterone assay applied together wilh vaginal cytology.